Rabies death in an adolescent tribal girl diagnosed postmortem, in Kerala - the precious life, preventable loss and equity concerns - Zinia T. Nujum; Pillaveetil Sathyadas Indu; Jeena Ramesh; Rekha Rachel Philip; Smitha S.; Seena. A. R.; Laila Raji N.; N. A. Balaram (BMC, 2024)
Abstract Background Rabies is a neglected tropical disease endemic in 150 countries, including India where it is present in all states and union territories except Andaman and Nicobar Islands Lakshadweep. Kerala reports high incidence of animal bites. This article discusses the preventable death of a 17-year-old tribal girl due to rabies in Kerala and the equity concerns it raises. Methods The case study was conducted using qualitative methods such as rapid key informant interviews, interactions in tribal assembly meetings, unstructured participant observations, and document verification. Thematic analysis was used, and the results are presented as an ethnographic summary with the use of quotes to substantiate the observations. Results The girl had gone to a town with her sister for a few days when she developed difficulty in eating, behavioral abnormalities, and injuries on her body. She subsequently died, and a post-mortem revealed Negri bodies in her brain, confirming rabies as the cause of death. The girl had been bitten by a puppy from the forest eight months prior, but she did not receive post-exposure prophylaxis. Multiple dogs are kept in each household in the settlement, and the community takes good care of them since they protect them from wild animals. However, awareness about the need for post-exposure prophylaxis is low, and access to it is difficult for this population. The social problems in the settlement affect their quality of life and their interactions with the outside world. Conclusions To prevent such deaths, it is essential to increase awareness and ensure equitable access to life-saving vaccines and immunoglobulin in hard-to-reach tribal areas. The cost-effectiveness of pre-exposure prophylaxis for children in high-risk areas such as this tribal settlement should be evaluated and compared with the WHO-recommended strategies of mass canine vaccination and One Health.